Evaluation of the time required to perform three retreatment techniques with dental microscope and ultrasonic activation for removing filling material from the oval root canal - Alakabani, Tarek-Fahed (J Clin Exp Dent, 2018)
BACKGROUND: When endodontic treatment fails, retreatment consists of the complete removal of the root canal filling material for thorough cleaning and reobturation. Various techniques are available for the filling removal procedure, which present varying degrees of efficacy, and take a varying length of time to perform. The aim of this study was to compare the time required to carry out reciprocating, rotary, and manual techniques with dental microscope and ultrasonic activation for removing filling material from root canals. MATERIAL AND METHODS: Ninety-nine extracted single-rooted teeth with straight and oval-shaped canals were selected. The samples were instrumented with ProTaper Gold System up to file F2 and obturated with AH Plus sealer and GuttaCore. The teeth were randomly divided into three groups (n=33) according to the instruments used for removal of filling material: Group (1) Reciproc blue R50 instrument; Group (2) ProTaper Retreatment instruments; Group (3) manual (Hedstrom files and Gates-Glidden drills), under dental microscope at X10 magnification with Ultrasonic retreatment tip. The time required to remove the filling materials was measured with a chronometer. Data were analyzed statistically applying the Kruskal-Wallis test followed by the Mann-Whitney U-test (p<0.05). RESULTS: The time required to remove filling material was significantly shorter in Group 1, followed by Group 2, the slowest being Group 3 (P<0.05). CONCLUSIONS: The reciprocating technique was the fastest method for removing root canal filling material. Key words:Endodontic retreatment, hedstrom file, ProTaper retreatment, reciproc blue.